2006
DOI: 10.1128/mcb.00312-06
|View full text |Cite
|
Sign up to set email alerts
|

Zebra Fish Dnmt1 and Suv39h1 Regulate Organ-Specific Terminal Differentiation during Development

Abstract: DNA methylation and histone methylation are two key epigenetic modifications that help govern heterochromatin dynamics. The roles for these chromatin-modifying activities in directing tissue-specific development remain largely unknown. To address this issue, we examined the roles of DNA methyltransferase 1 (Dnmt1) and the H3K9 histone methyltransferase Suv39h1 in zebra fish development. Knockdown of Dnmt1 in zebra fish embryos caused defects in terminal differentiation of the intestine, exocrine pancreas, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
141
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(154 citation statements)
references
References 60 publications
13
141
0
Order By: Relevance
“…TET: Ten-eleven translocation. [8][9][10], and exists predominantly at cytosines within CG dinucleotides. The reason why CG is favored over other nucleotide contexts relates to its palindromic nature.…”
mentioning
confidence: 99%
“…TET: Ten-eleven translocation. [8][9][10], and exists predominantly at cytosines within CG dinucleotides. The reason why CG is favored over other nucleotide contexts relates to its palindromic nature.…”
mentioning
confidence: 99%
“…30,31 In Kaiso-depleted frog and zebrafish, the embryos exhibited failure to develop normal dorsal structures, including axial defect and incomplete head formation, 30,31 the features similar to the phenotype associated with Dnmt1 depletion in zebrafish. 37 These observations suggest the possibility that Kaiso is involved in inhibiting the expression of methylated ntl/Xbra during early embryogenesis. In this study we demonstrated that in the gynogenetic haploid, which inherited only the methylated maternal ntl allele, the insufficiency of ntl expression during early embryogenesis and the failure of anterior notochord formation due to the absence of the unmethylated paternal ntl allele were rescued by removing the methyl-CpG dependent transcriptional repressor Kaiso.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 90%
“…There are three DNMT families in vertebrates: DNMT1, DNMT2, and DNMT3 (Goll and Bestor, 2005). DNMT1 is implicated in maintaining existing methylation patterns as well as on the regulation of histone methylation (Rai et al, 2006). The functional importance of DNMT2 in vertebrates is largely unclear.…”
Section: Dna Methylationmentioning
confidence: 99%
“…The functional importance of DNMT2 in vertebrates is largely unclear. However, a recent study in zebrafish demonstrated its involvement in cytoplasmic RNA methylation (Rai et al, 2006). On the other hand, both DNMT3A and 3B have been demonstrated to be essential for de novo methylation throughout embryonic cell differentiation (Chen et al, 2003;Goll and Bestor, 2005;Reik, 2007).…”
Section: Dna Methylationmentioning
confidence: 99%